Strategic plan for Community Health Development Cooperative Hospital - Jaranilla, Jasmin C. (School of Management, University of the Philippines Mindanao, 2007)
This paper presents a proposed strategic plan for Community Health and Development Cooperative Hospital (CHDCH), a healthcare service provider for more than 10 years. It is based on analysis on the hospital?s performance for the last 5 years, potential developments in its external environment for 2008 to 2012, as well as its cooperative objectives. While effective marketing is partially helping to sustain revenues for the hospital, the shortage of medical staff and hospital rooms as well as viability to fully maximize some of its facilities continue to be a source of concern. The analytical tool used in the strategic management framework of Fred David as modified by Prof. Miguel D. Soledad. The data were gathered through interviews, Minutes of the General Meetings and financial reports of the hospital from 2002-2006. These are two strategies being used to respond to the internal and external environments: Market Development and Cost Leadership. Market development presents products, often with cosmetics modifications, to customers in related market area by adding channels of distribution or by changing the content of advertising or promotion. Cost leadership directs its resources to the profitable growth of a single product, in a single market, with a single dominant technology. The formulation of the strategies was based on the analysis from SWOT, IFE and EFE Matrices. SWOT matrix is the most widely used strategic planning matrix among companies and organizations. This matrix identifies the company?s strengths, weaknesses, opportunities and threats. It enables the company to generate strategies based on important underlying factors. IFE Matrix focuses on the internal environment of the company while EFE Matrix highlights the external environment of the business. The IFE and EFE Matrices shows performance of the company in a micro level and benchmarks its competitiveness to the industry. The strategic goals were created based on results extracted from the analytical tools used. Implementation of strategic goals was organized according to functional area, officers responsible for the implementation and monitoring system. Control system purposes the Audit and Inventory System. It is a monitoring and control system that reviews on operation per functional area. Performance indicators uses the Cooperative Development Authority?s COOP Peso Evaluation Form. It is a standardized form used by all cooperatives to measure financial stability and operations performance. The hospital information system is part of the program of the Department of Health to ensure quality service is adopted.